Short Communication: Effects of temperature on growth, pigment composition and protein content of an Antarctic Cyanobacterium Nostoc commune - RANJANA TRIPATHI; UMESH P. DHULDHAJ; SURENDRA SINGH (Smujo International, 2012)
Abstract. Tripathi R, Dhuldhaj UP, Singh S. 2012. Short Communication: Effects of temperature on growth, pigment composition and protein content of an Antarctic Cyanobacterium Nostoc commune. Nusantara Bioscience 4: 134-137. Effect of temperature variation on biomass accumulation, pigment composition, and protein content was studied for the cyanobacterium Nostoc commune, isolated from Antarctica. Results confirmed the psychrotrophic behavior (optimum growth temperature 250C) of the cyanobacterium. Low temperature increased the duration of lag phase and exponential growth phase. Maximum increase in biomass was recorded on 24th day at 250C and on 12th day at 50C. The downshift from 25 to 50C had almost negligible effect on chl a content. Maximal protein content was recorded for cultures growing at 50C on 12th day. The carotenoids/chl a ratio was maximum (2.48) at 50C on 9th day. It remained almost constant for cultures growing at 5 and 350C. There was an induction in protein synthesis following downshift in temperature from 25 to 5?C.